OPTIMASI PENENTUAN KESEPAKATAN HARGA NILAM PADA RANTAI PASOK MINYAK ATSIRI DI KABUPATEN KUNINGAN - Hendrastuti Hendrastuti; Eriyatno Eriyatno; Meika Syahbana Rusli; Johny Wahyuadi Soedarsono (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Patchoulioilis one of thevolatile oilcommodityIndonesia. Development of patchouli oil industry not only improves the welfare of agroindustry entrepreneurs, but also will improve the welfare of patchouli plant growers. The purpose of this research is to design a Balancing of the Selling Price of patchouli oil and patchouli by price optimization andFeasibility Analysis of small farming and refining industries by analysis of financial feasibility.Feasibility Farm and Small business feasibility Refining Industry are viable(IRR 1.0 and B / C Ratio 1.0)